Characterization of extracellular chitin deacetylase from Aneurinibacillus aneurinilyticus isolated from marine crustacean shell - Poonam Das; Manisha Das; Sheela Kumari Sahoo; Jagneshwar Dandapat; Jyotsnarani Pradhan (Current Research in Microbial Sciences)
Chitosan is a promising biopolymer with wide range of applications. It is the deacetylated product of chitin. Commercially, it is produced from chitin via a harsh thermochemical process that has several shortcomings and heterogenous deacetylation product. Chitin can be transformed into chitosan through enzymatic deacetylation using chitin deacetylase (CDA), enabling the production of chitosan with a specific degree of deacetylation. CDA is primarily extracted from fungi followed by bacteria and insects. The extraction of CDA from fungus is more complex, possess several health risks for human including skin lesions. Therefore, screening of potent bacterial CDA is the need of the hour. In this study, for the first time we have isolated a bacterial strain Aneurinibacillus aneurinilyticus from the rinsed water of marine crab shell, and it was found to be a potent CDA producer. The extracellular CDA from A. aneurinilyticus has been partially purified and the specific activity of the enzyme was found to be 569.73 U/ mg protein. SDS-PAGE profiling of the purified sample depicts two isomers of CDA with molecular weights of 27 kD and 45 kD. The pH and temperature optima of the purified CDA were found to be 7.4 and 37 °C, respectively. The partially purified enzyme has Km and Vmax values of 98.455 µM and 909.09 µmole/min, for non-chitinous substrate such as p-nitroacetanilide. For chitinous substrates like glycol chitin, N-acetyl glucosamine hexamer and colloidal chitin, the enzyme exhibited Km of 96.96, 111.75 and 127.86 µM, respectively, Vmax for these substrates were 23.31, 10.12 and 10.772 µmole/min, respectively. Metal ions like Mn and Mg considerably boost the production and activity of CDA, whereas Cd and Co strongly inhibit its activity. Insights from this study further substantiate that this enzyme follows Michaelis-Menten equation and has potential for industrial applications.